1998
DOI: 10.1103/physrevb.58.15208
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic effects of Sr substitution for Ba inY(Ba1xSrx

Abstract: To unveil the structural mechanisms associated with T c variations induced by either mechanical or chemical pressure, samples of the Y(Ba 1Ϫx Sr x ) 2 Cu 3 O w system with xр0,0. 02,0.1,0.25,0.35,0.5,0.625,0.75,1, as well as those with xϭ0.5 and wϭ6.685,6.80,6.96,6.98, have been prepared and characterized. Characterization includes crystal structural refinements based on powder neutron diffraction data taken at room temperature, electron microscopy for detecting a possible Ba/Sr ordering, and resistive and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 26 publications
7
37
1
1
Order By: Relevance
“…Secondly, we focus on the effects of strain on Schottky defects and related phenomena for a series of homovalent substitutions at Y and Ba sites of YBa 2 Cu 3 O 7−δ . Although the 123 structure is not stable in the Ca-and Sr-analogs under ambient pressure [23,24,25], partial substitution of Sr on the Ba site has been reported [4,23,26,27,28]. Finally, strain effects on chain-oxygen order-disorder transition of REBa 2 Cu 3 O 7−δ will be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we focus on the effects of strain on Schottky defects and related phenomena for a series of homovalent substitutions at Y and Ba sites of YBa 2 Cu 3 O 7−δ . Although the 123 structure is not stable in the Ca-and Sr-analogs under ambient pressure [23,24,25], partial substitution of Sr on the Ba site has been reported [4,23,26,27,28]. Finally, strain effects on chain-oxygen order-disorder transition of REBa 2 Cu 3 O 7−δ will be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in many bulk forms and multilayer applications, Y is replaced by Nd, Sm, or other rare-earth elements (RE). Doping YBa 2 Cu 3 O 7−δ with Ca, Sr, or other alkaline earth elements (AE) has also been shown to improve bulk and grain boundary transport and other properties [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated in Fig. 7 system, the very first NPD study using a sample with y = 0.5 (z not given) concluded full ordering of the oxygen vacancies [33], but later Licci et al [24] revealed partial shift of the charge-reservoir oxygen from the b-axis site to the a-axis site due to Sr substitution. Thermoelectric power measurement has proven to be a powerful tool to reveal the metallicity of (fully-oxygenated) CuO chains in Cu-1212 and related copper oxides [36 -38].…”
Section: Resultsmentioning
confidence: 99%
“…The H irr value was determined by the procedure introduced elsewhere [23]. In brief, the magnetic field (H) In a previous study on Cu(Ba,Sr) 2 YCu 2 O 6+z samples Licci et al [24] used (x, 1/2, 0) rather than the conventional position of (0, 1/2, 0) for the O (1) site. This was also tested in the present work, but no improvements were seen in the reliability factors, R p , R wp and χ 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The H irr value was determined by the procedure introduced elsewhere [23]. In brief, the magnetic field (H) In a previous study on Cu(Ba,Sr) 2 YCu 2 O 6+z samples Licci et al [24] used (x, 1/2, 0) rather than the conventional position of (0, 1/2, 0) for the O (1) site. This was also tested in the present work, but no improvements were seen in the reliability factors, R p , R wp and χ …”
Section: Methodsmentioning
confidence: 99%